AN ANALYSIS OF ILLOCUTIONARY ACTS PERFORMED BY THE MAIN CHARACTER IN DIVERGENT MOVIE BY NEIL BURER 2014 (PRAGMATIC APPROACH) - Lelet, Irene Trivena; Olii, Sanerita T.; Kumayas, Tirza (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The research is pragmatics approach study of An Analysis of Illocutionary Acts Performed by the Main Character in Divergent Movie. The objectives of this researcher are to find out the types of illocutionary acts are performed by the main character’s utterance, and to find out dominantly of types of illocutionary acts are used by the main character’s utterance. The researcher uses the descriptive qualitative method to describe and analyze the selected of illocutionary acts which are watching a movie and then classifies them according to John R. Searle’s concept types of illocutionary acts. The technique of collecting data are (1) watching the movie for several times in order to understand the whole story (2) collecting the data, transcribing the data from the dialogue in the movie into form of list, and identifying the listed dialogue that contain types of illocutionary acts carried out by the participant (3) finding out the types of illocutionary acts carried out by the participant representative, directive, commissives, expressive, and declarative. The researcher uses content analysis which focus on analyzing types of illocutionary acts and the dominant of types of illocutionary acts in Divergent movie carried out by the main character.